Transcriptomics and in vivo tests reveal novel mechanisms underlying endocrine disruption in an ecological sentinel, Nucella lapillus. Issue 6 (3rd December 2012) - Pascoal, Sonia; Carvalho, Gary; Vasieva, Olga; Hughes, Roger; Cossins, Andrew; Fang, Yongxiang; Ashelford, Kevin; Olohan, Lisa; Barroso, Carlos; Mendo, Sonia; Creer, Simon
Abstract Anthropogenic endocrine disruptors now contaminate all environments globally, with concomitant deleterious effects across diverse taxa. While most studies on endocrine disruption (ED) have focused on vertebrates, the superimposition of male sexual characteristics in the female dogwhelk, Nucella lapillus (imposex), caused by organotins, provides one of the most clearcut ecological examples of anthropogenically induced ED in aquatic ecosystems. To identify the underpinning mechanisms of imposex for this 'nonmodel' species, we combined Roche 454 pyrosequencing with custom oligoarray fabrication inexpensively to both generate gene models and identify those responding to chronic tributyltin (TBT) treatment. The results supported the involvement of steroid, neuroendocrine peptide hormone dysfunction and retinoid mechanisms, but suggested additionally the involvement of putative peroxisome proliferator–activated receptor (PPAR) pathways. Application of rosiglitazone, a well‐known vertebrate PPARγ ligand, to dogwhelks induced imposex in the absence of TBT. Thus, while TBT‐induced imposex is linked to the induction of many genes and has a complex phenotype, it is likely also to be driven by PPAR‐responsive pathways, hitherto not described in invertebrates. Our findings provide further evidence for a common signalling pathway between invertebrate and vertebrate species that has previously been overlooked in the study of endocrine disruption.